E-Procurement and Company Performance: A Quantitative Analysis of the Textile Industry of Pakistan - Kumar, Prince; Aziz, Shahid; Khan, Abdullah Muhammad (2023)
The current study investigated the impact of top management support (TMS), technological factors and information quality (IQ) on implementation of e-Procurement leading towards company performance (CP) in the textile sector of Pakistan. 202 SC professionals and executives have participated in the data collection based on nonprobability purposive sampling technique using a five-point Likert scale questionnaire. Moreover, PLS-SEM technique has been used for data analysis. The findings showed that the implementation of eProcurement is positively impacted by top management support, technological factors, and information quality. Additionally, it has been discovered that eProcurement implementation of eProcurement has a favorable impact on business performance. Companies should provide training for workers involved in e-Procurement in order to raise the quality of information used to evaluate and improve business performance. E-Procurement adoption can be affected by a number of factors, one of which is the skills of the staff.